Efeitos da solicitação e de subsequente descrição dos relatos verbais de um terapeuta sobre seu desempenho em sessões posteriores - Amaral, Sueli de Sousa (2010)
The present study had the purpose to verify if a report request from a therapist s verbal report classes on ongoing clinical counseling could affect his performance on future therapeutic sessions, as suggested in literature. Therefore, a procedure from an early study was replied apart from changes on the response classes investigated. One psychology therapist and one client participated in this study and 11 counseling sessions were recorded on video. The therapist s verbal responses were categorized according to the Multidimensional System For Coding Behaviors In Therapist-Client Interaction and measured by occurrences. The therapist s verbal responses were requested after the fourth and eighth sessions concerning previous sessions and categorized as analysis reflexion request and recommendation. The results confirm the replied study suggesting that reports request can modify the therapist behavior in future sessions. It was identified a low correspondence between observed and reported verbal responses differently from previous study. The research line seems relevant for providing knowledge regarding the verbal processes that interfere on therapists behavior when submitted to supervision sessions and probably the clients behavior in counseling sessions